Pengaruh Nonmonotonic Kepemilikan Manajerial Pada Nilai Perusahaan - Ramadhoan, Nurul Islamiah; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2015)
This study aims to find out the effect of managerial ownership on firm value, low managerial ownership on firm value and high managerial ownership on firm value. This research was conductedat themanufacturing companies listed in Indonesia Stock Exchange(IDX) 2011-2013. The numberof samples taken 129 samples by purposive sampling method. Methods of data collectionis bya nonparticipantobservationmethod. The analysis techniqueusedis multiple linear regression. The result foundtheeffect of managerialownershipon firm value, low managerial ownershi pnegatively affectthe value ofthe company, andhighmanagerialownershiphas positive effecton firm value
Keywords: Enterprisevalue, Managerial Ownership, Non-monotonic